Self-organized CAC mechanism adopting for self-similarity service in wireless network - Lei FENG; Wen-jing LI; Xue-song QIU (Tongxin xuebao)
To improve the access capacity in wireless network with the QoS ensuring,the service similarity in the wireless network was researched,and the service bandwidth was calal with similarity and QoS parameters.Then an SS-CAC (self-organized based on network similarity call admission control) mechanism based on the service bandwidth optimization was introduced to lower the system bandwidth utilization and service rejection probability.And the novel mechanism was achieved and simulated.Compared with traditional CAC,the results of simulation show the performance of SS-CAC mechanism can not only ensure the quality of the voice service but also reduce the bandwidth utilization of the data service by 2.69%.In addition,it can also reduce the call rejection ratio and call drop ratio by 0.95% and 2.81% respectively in the case of high cell load.